Diversification of Funding Models of Higher Education Service Market in Georgia - Kikutadze, Vasil; Tabatadze, Lasha (European Scientific Journal, ESJ, 2017)
Georgia’s European choice and the desire to get closer to European standards make the country face the particular challenges. According to the value and scale of changes, higher education service market occupies the specific place. Higher education services market as the core resource of the formation of professional staff, presents a key factor for sustainable and dynamic business development. On the basis of the aforementioned, in Georgia, it is especially important to promotion the diversification of funding for higher education market.